Estudos toxicológicos pré-clínicos e antitumorais do extrato acetônico das folhas de Annona muricata L. - Oliveira, Cecília Carvalho de (2012)
Annona muricata, popularly known as soursop in Brazil, is a plant widely used in vernacular medicine as teas and infusions for the treatment of various diseases, including cancer. This study aimed to evaluate the toxicological, genotoxicological and antitumor profile of the acetone extract from the leaves of Annona muricata and test it using short-and long-term in vivo and in vitro assays. We initially assessed in vitro cytotoxicity against several human tumor cell lines. There was a toxic response to many of them, especially K-562, HCT-8, HCT-116 and SF-295 with average inhibitory concentration (IC50) of 0.1452 µg/mL, 0.2457 µg/mL, 0.2956 µg/ml and 0.2191 µg/mL respectively. Acute toxicity studies were performed in vivo and the average lethal dose (LD50) was 310.2 mg/kg. Chronic toxicity studies were performed using doses of 12.5 mg/kg, 25 mg/kg and 50 mg/kg of acetone extract. Results showed little change in animals’ physical, biochemical and hematological parameters, showing that the extract is well tolerated and not very toxic. Genotoxicity studies were performed in vivo. Animals were given three oral doses of the acetone extract (12.5 mg/kg, 25 mg/kg and 50 mg/kg). After 24 and 48 hours peripheral blood and bone marrow were collected. In the comet assay no high grade comet was detected and tested doses were statistically similar to the negative control. In the micronucleus test, none of the tested acetone extract doses induced the formation of micronuclei. They were statistically similar to the negative control, unlike what was observed in the positive control. Antitumor testing showed that the extract has tumor growth inhibitory activity, both in rats, in the Walker 256 carcinosarcoma model, and in mice, in the Sarcoma 180 model. All such results indicate that the acetone extract from the leaves of Annona muricata has little toxic action and significant activity inhibiting tumor growth in the models we tested.